A critical analysis of rationalisation and redeployment of educators in Limpopo Province - Mabotja, Morema Jack (My University, 2016)
Refer to document
Thesis (M. Ed. (Curriculum Studies)) -- University of Limpopo, 2016
Keywords: Redeployment; Educators; Teachers -- Employment -- South Africa; Teacher transfer; Teachers -- Selection and appointment -- South Africa -- Limpopo; Teachers -- Supplementary employment